UNIT 17.18 Glycosylation Analysis for Congenital Disorders of Glycosylation. (1st July 2015) - Li, Xueli; Raihan, Mohd A.; Reynoso, Francis Jeshira; He, Miao
Abstract : Congenital disorders of glycosylation (CDG) are a group of diseases with highly variable phenotypes and inconsistent clinical features. Since the first description of a CDG in 1980, approximately 100 disorders have been identified. Most of these are defects in protein glycosylation, although an increasing number are defects of glycolipid or proteoglycan biosynthesis. A group of biochemical markers has been used to characterize protein glycosylation abnormalities in CDG. This unit describes three protocols that can be used to measure plasma or serum carbohydrate deficient transferrin (CDT) profile, N‐glycan profile, and O‐glycan profile by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) or liquid chromatography‐electrospray ionization‐tandem mass spectrometry (LC‐ESI‐MS). The quantification of particular biomarkers, such as T antigens or sialylated T antigens, could also be achieved by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). These techniques can be used to identify a majority of patients with defects in protein glycosylation, although different techniques, such as flow cytometry with immunostaining, are necessary to detect defects in glycolipid or proteoglycan biosynthesis which is not included in this unit. © 2015 by John Wiley & Sons, Inc.